ChemInform Abstract: Highly Selective Trifluoroacetic Ester/Ketone Metathesis: An Efficient Approach to Trifluoromethyl Ketones and Esters. Issue 51 (23rd December 2014) - Zhou, Yuhan; Yang, Dongmei; Luo, Gen; Zhao, Yilong; Luo, Yi; Xue, Na; Qu, Jingping
Abstract Enolizable alkyl aryl ketones react with ester (II) to produce the 2 types of title compounds.